Characterization and phylogenetic analysis of the complete mitochondrial genome of Stephnometra indica (Pelmatozoa: Crinoidea). Issue 2 (3rd July 2019) - Ma, Shaobo; Zhang, Huixian; Wang, Xin; Yin, Jianping; Shen, Pingping; Lin, Qiang
Abstract: The crinoid Stephnometra indica inhabits coral reefs and surrounding waters in the western Pacific Ocean. In this study, the complete mitochondrial genome of S. indica (15, 878 bp) was confirmed to contain 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes. The gene order of S. indica was identical to that of previously published Crinoidea. The nucleotide composition of the S. indica mitogenome was biased toward A + T nucleotide 73.68%. There were four unassigned regions (UASs) found in S. indica and all four UAS regions were AT-biased. The phylogenetic relationship illustrated that S. indica is more closely related to Antedon mediterranea within the family Crinoidea.